Dignity and Deferral Narratives as Strategies in Facilitated Technology-Based Support Groups for People with Advanced Cancer. (22nd February 2012) - Street, Annette F.; Wakelin, Kate; Hordern, Amanda; Bruce, Nicola; Horey, Dell
Abstract : This paper examines the value of facilitated telephone and online support groups for palliative care. Telephone interviews were conducted with twenty people living with advanced cancer who had participated in either a telephone or online support group facilitated by the Cancer Council Victoria, Melbourne, Australia. Two dominant participant narratives emerged: a focus on dying with dignity or an interest in deferring discussion of death and dying to focus on the present. Despite the different approaches, participants found the technology-based support groups to be accessible and safe environments in which to discuss difficult topics in privacy. Technology-based strategies provide opportunities for health professionals to provide social and emotional care to more people by moving beyond individualised care and facilitate peer-to-peer support at the end of life, especially to those with specific needs. Such options are feasible for palliative care services to set up and acceptable to a group of clients, especially for younger clients or those socially or geographically isolated.